Things fall apart - Achebe, Chinua (Penguin Modern classics, 2001)
Okonkwo is the greatest wrestler and warrior alive, and his fame spreads throughout West Africa like a bush-fire. But when he accidentally kills a clansman, things begin to fall apart. Then Okonkwo returns from exile to find missionaries and colonial governors have arrived in the village.